2005
DOI: 10.1001/archpsyc.62.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of DSM-IV Disorders and Attendant Help-Seeking in 2 American Indian Reservation Populations

Abstract: Alcohol disorders and posttraumatic stress disorder were more common in these American Indian populations than in other populations using comparable methods. Substantial comorbidity between depressive and/or anxiety and substance disorders suggests the need for greater coordination of treatment for comorbid disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
209
4

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 256 publications
(222 citation statements)
references
References 33 publications
9
209
4
Order By: Relevance
“…1,28 Although we found few ethnic differences and very small effect sizes for between group differences, most of these were in the direction of greater pathology in the AI/NA sample compared with the white sample and warrant consideration of the possibility that eating pathology is more prevalent in AI/NA populations, similar to other mental health problems. 29 Whereas most of the study data reflect point prevalence, we also assessed lifetime prevalence of having received an eating disorder diagnosis. A substantial number of AI/NA women had been told by a doctor that they had an eating disorder; this prevalence was comparable to that of white female study participants and is also consistent with epidemiological surveys of predominantly white samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,28 Although we found few ethnic differences and very small effect sizes for between group differences, most of these were in the direction of greater pathology in the AI/NA sample compared with the white sample and warrant consideration of the possibility that eating pathology is more prevalent in AI/NA populations, similar to other mental health problems. 29 Whereas most of the study data reflect point prevalence, we also assessed lifetime prevalence of having received an eating disorder diagnosis. A substantial number of AI/NA women had been told by a doctor that they had an eating disorder; this prevalence was comparable to that of white female study participants and is also consistent with epidemiological surveys of predominantly white samples.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although there has been extensive research about mental health problems among Indigenous peoples of the US, including a large scale epidemiological study focused exclusively on relatively homogenous cultural subgroups, 29 such prior work did not include items measuring eating disorders. As such, the Add Health sample offers an important, albeit preliminary, glimpse into the problem of eating pathology among AI/NA young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, others have found that minority group members have equal or better mental health than White Americans (Beals et al, 2005;McGuire & Miranda, 2008); however, the psychological symptoms for those with mental health diagnoses are often worse (U.S. Department of Health and Human Services, 2001).…”
Section: Mental Healthmentioning
confidence: 99%
“…AI-SUPERPFP surveyed a stratified random sample of 3084 American Indians (Beals et al, 2003;Beals et al, 2005), 2878 (93.3%) of whom answered the three distinct sets of service utilization questions described later. The populations of inference were 15-to 54-year-old enrolled members of two closely related Northern Plains tribes and a South-west tribe living on or within 20 miles of their respective reservations at the time of sampling (1997).…”
Section: American Indian Service Utilization and Psychiatric Epidemiomentioning
confidence: 99%
“…Sample weights, used in all inferential analyses presented here, accounted for differential selection probabilities across all strata and for patterns of non-response. Detailed information regarding the design and methods utilized in AI-SUPERPFP are described elsewhere (Beals et al, 2003;Beals et al, 2004;Beals et al, 2005). The diagnostic interview utilized in AI-SUPERPFP was a version of the NCS University of Michigan version of the Composite International Diagnostic Interview (UM-CIDI) adapted for use in American Indian communities in the context of a previous study (Beals et al, 2002).…”
Section: American Indian Service Utilization and Psychiatric Epidemiomentioning
confidence: 99%